Pelatihan Pengembangan Media Pembelajaran Interaktif Berbasis Augmented Reality (AR) bagi Guru Bahasa Jerman untuk Meningkatkan Kompetensi Literasi Digital - Serpara, Henderika; Wenno, Crystle (Jurnal Pengabdian Arumbai, 2025)
The development of digital technology requires teachers to adapt and integrate technology-based innovations to make learning more interactive and relevant. This community service program aimed to enhance digital literacy and the capacity of German language teachers in Ambon to develop interactive learning media using Augmented Reality (AR). The participatory method involved stages of needs assessment, technical training, mentoring, and implementation evaluation. The results revealed a 25.8% improvement in digital literacy and 93% achievement in AR media production competence. Teachers successfully created thematic AR-based German learning media that effectively increased student engagement and motivation. This program contributes to advancing teacher professionalism and fostering educational innovation through technology in island regions. Recommendations emphasize the importance of continuous training across disciplines to strengthen digital literacy culture within educational institutions.